Role Of Law And Social Stratification For Online Taxibike Consumer According To The Republic Of Indonesia Law Number 8 1999 Considering Consumer Protection - Evidiannita Candrawati; Rini Kusnari; Hermi Hermi; Nur Joko Sariono; Dwi Tatak Subagiyo (LPPM of NAROTAMA UNIVERSITY, 2021)
The role of law and social stratification for online taxi bike consumers regarding implementation Law No. 8 of 1999, using normative descriptive methods. The Law uncurtained concerning taxi bike position as a transportation mode. And since motorbike is likely uncommonly used public transportation. Not only for the taxi bike driver in general, but this issue is also addressed to Gojek driver since the main service of Gojek is using a motorbike as made of transportation. Regarding the after-mentioned issue, according to article 1 1 of Law No. 8 of 1999 on Consumer Protection (BFL) on 20 April 1999(Indonesia, 1999) it is obvious that the relation of online taxi bike system is so relevant, observe by social stratification approach since it is hierarchically structured. Thus causing a relationship between law and social stratification as are chain reactive it is stated within by the law. There is existing discrimination in public caused by social discrimination that can be legally overcome, and law guarantees equality for all.